Lithium and its isotopic ratio ⁶Li/⁷Li in the atmospheres of sharp-lined roAp stars γ Equulei and HD 166473 - Shavrina, A.; Polosukhina, N.; Khan, S.; Pavlenko, Ya.; Khalack, V.; Wade, G.A.; Quine, t P.; Mikhailitska, N.; Yushchenko, A.; Gopka, V.; Kudryavtsev, D. (Кинематика и физика небесных тел, 2005)
The lithium lines at 6708 Å for two sharp-lined roAp stars γ Equ and HD 166473 and at 6103 Å for γ Equ were analyzed in high resolution spectra. Three spectral synthesis codes – STARSP, ZEEMAN2, and SYNTHM – were used. New lines of the rare-earth elements from the DREAM database and lines calculated on the basis of the NIST energy levels were included. Magnetic splitting and other line broadening processes were taken into account. Enhanced abundances of lithium in the atmospheres of the stars and high estimates of ⁶Li/⁷Li ratio (0.2 ÷ 0.5) can be explained by the Galactic Cosmic Ray (GCR) production due to spallation reactions and the preservation of original ⁶Li and ⁷Li by strong magnetic fields.